Dakwah dan Transformasi Sosial dalam Perspektif Al-Qur’an - Sulaiman (4, 2026)
This study discusses da'wah and social transformation from a Qur'anic perspective. Da'wah is not only understood as the verbal transmission of Islamic teachings, but also as a process of social change aimed at building a society that is faithful, moral, just, and harmonious. The Qur'an provides guidance that social change must be carried out through a wise, humanistic, and exemplary approach, as reflected in the principles of da'wah bil hikmah (intelligible), mau'izhah hasanah (intelligible), and mujadalah billati hiya ahsan (intelligible). This study employed a library research method with a descriptive-qualitative approach through analysis of Qur'anic verses related to da'wah and social change, supported by various tafsir (interpretative) literature and Islamic studies. The results indicate that da'wah plays a strategic role as an instrument of social transformation in shaping individual behavior and improving social order. Social transformation, from a Quranic perspective, is not only oriented toward material change, but also toward moral, spiritual, and cultural change based on the values ​​of monotheism, justice, brotherhood, and humanity. Furthermore, the success of da'wah in realizing social transformation is greatly influenced by the exemplary conduct of the da'i, the relevance of da'wah methods to societal conditions, and the da'wah's ability to respond to the challenges of the times. Thus, da'wah, from a Quranic perspective, is a crucial tool for creating constructive and sustainable social change in modern society. Abstrak Penelitian ini membahas tentang dakwah dan transformasi sosial dalam perspektif Al-Qur’an. Dakwah tidak hanya dipahami sebagai aktivitas penyampaian ajaran Islam secara verbal, tetapi juga sebagai proses perubahan sosial yang bertujuan membangun masyarakat yang beriman, berakhlak, adil, dan harmonis. Al-Qur’an memberikan pedoman bahwa perubahan sosial harus dilakukan melalui pendekatan yang bijaksana, humanis, dan penuh keteladanan sebagaimana tercermin dalam prinsip dakwah bil hikmah, mau‘izhah hasanah, dan mujadalah billati hiya ahsan. Penelitian ini menggunakan metode kajian pustaka (library research) dengan pendekatan deskriptif-kualitatif melalui analisis terhadap ayat-ayat Al-Qur’an yang berkaitan dengan dakwah dan perubahan sosial, serta didukung oleh berbagai literatur tafsir dan kajian keislaman. Hasil penelitian menunjukkan bahwa dakwah memiliki peran strategis sebagai instrumen transformasi sosial dalam membentuk perilaku individu dan tatanan masyarakat yang lebih baik. Transformasi sosial dalam perspektif Al-Qur’an tidak hanya berorientasi pada perubahan material, tetapi juga perubahan moral, spiritual, dan budaya yang berlandaskan nilai-nilai tauhid, keadilan, persaudaraan, dan kemanusiaan. Selain itu, keberhasilan dakwah dalam mewujudkan transformasi sosial sangat dipengaruhi oleh keteladanan da’i, relevansi metode dakwah dengan kondisi masyarakat, serta kemampuan dakwah dalam menjawab tantangan zaman. Dengan demikian, dakwah dalam perspektif Al-Qur’an menjadi sarana penting dalam menciptakan perubahan sosial yang konstruktif dan berkelanjutan di tengah kehidupan masyarakat modern.